2019
DOI: 10.4236/ojss.2019.911013
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Plant Responses to Soil Salinity and Amelioration Strategies

Abstract: Soil salinity is a major abiotic stress, limiting plant growth and development worldwide. Plants grown under saline soil condition experiences a significant amount of high osmotic stress, ion toxicities and nutritional disorder, and these are responsible for poor soil physical condition as well as lead to reduced plant productivity. Plants exhibit a number of responses under salt stress by affecting morphological, physiological and biochemical process. A complete understanding of how plants respond to soil sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 53 publications
(60 reference statements)
0
33
0
Order By: Relevance
“…These reports suggest that most of the agronomically important crop species are not compatible with high salt levels, as uttered in a review by Parihar et al [ 4 ]. Furthermore, the Food and Agriculture Organization (FAO) reports stated that salinity is a serious threat to over 6% of the world’s land [ 4 ] and the relevant reports anticipate that salinity will severely affect more than 50% of arable land by 2050 [ 9 ]. For this reason, the use of new methods and strategies to decrease the negative effects of salinity has gained great importance.…”
Section: Introductionmentioning
confidence: 99%
“…These reports suggest that most of the agronomically important crop species are not compatible with high salt levels, as uttered in a review by Parihar et al [ 4 ]. Furthermore, the Food and Agriculture Organization (FAO) reports stated that salinity is a serious threat to over 6% of the world’s land [ 4 ] and the relevant reports anticipate that salinity will severely affect more than 50% of arable land by 2050 [ 9 ]. For this reason, the use of new methods and strategies to decrease the negative effects of salinity has gained great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Under salt stress conditions, plants are increase the uptake of Na + ions that affected uptake of other ions like K + that leads to cause the K + deficiency resulting the lowering of K + /Na + ratio (Kibria et al, 2017). Salt stress induced the significant changes in physiological and biochemical conditions in plant, for example.…”
Section: Mechanism Of Plant Responses and Adaptation To Soil Salinitymentioning
confidence: 99%
“…Salt stress induced the significant changes in physiological and biochemical conditions in plant, for example. decrease in protein synthesis, lower level of leaf chlorophyll content, increased ROS accumulation, changes in antioxidant enzymatic activities, enhanced accumulation of compatible solutes such as proline, glycine betaine, sorbitol, mannitol, pinitol and sucrose (Figure 2) (Kibria, Hoque, 2019).…”
Section: Mechanism Of Plant Responses and Adaptation To Soil Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Salt stress hampers plant progress and limits yield by interfering photosynthetic rate (7) and accumulation of toxic such as Na + and Clions (8). Several studies reported soil salinity decreased chlorophyll content (9), increased ROS (10), nutritional disorder (11) and ionic imbalance in plants (12), which finally contributed to significant yield loss (13).…”
Section: Introductionmentioning
confidence: 99%